118k views
2 votes
Simplify.


( { - 2})^( - 3)
options:

8

1/8

-8

-1/8​

User Avolkmann
by
5.4k points

2 Answers

4 votes

Answer:

-1/8

Explanation:

Apply exponent rule ^a^-b = 1/a^B

User Zachary Weixelbaum
by
4.8k points
1 vote


\huge\textsf{Hey there!}


\large\textsf{2}\mathsf{^(-3)}\\\\\\\mathsf{= (1)/(-2*-2*-2)}\\\\\\\mathsf{-2*-2*-2 =\bf (-2)^(3)}\\\\\mathsf{(-2)^3}\\\mathsf{= -2*-2*-2}\\\mathsf{= 4*-2}\\\mathsf{\mathsf{= \bf -8}}\\\\\\\mathsf{= -2^(-3) \rightarrow\boxed{\bf -(1)/(8)}}\large\checkmark


\boxed{\boxed{\large\textsf{Answer: Option D. }\mathsf{\bf - (1)/(8)}}}\huge\checkmark


\large\textsf{Good luck on your assignment and enjoy your day!}

~
\frak{Amphitrite1040:)}

User MkMan
by
6.3k points